DETERMINATION OF RISK FACTORS FOR THE POWER LINE POLES PRODUCTION PROCESS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Today is necessary to solve many tasks related to manufacturing. It is necessary to perform activities in the environmental area. This process is related by management o f the activities o f products or service that impact the environment. The manufacturing process of wood poles is connected with possibility o f the environmental emergency because high toxic and reactive substances are used in the technology. The objective o f the report is to determine the factors of the technological process related to ecological hazard. The initiator events of emergency that are related to maintenance of technological machinery are analysed in the report. For analyses ofpossible machinery damages the methods o f hazard analyses are offered. Calculation are offered for possible emergency analyse, the methods of hazard analyses are offered and the effectiveness of specific methods related to problems of environmental defensive are analysed in the report.